Tobacco-Derived Lipopolysaccharide, Not Microbial Translocation, as a Potential Contributor to the Pathogenesis of Rheumatoid Arthritis - Meyer, Pieter W. A.; Ally, Mahmood M. T. M.; Tikly, Mohammed; Tintinger, Gregory; Winchow, Lai Ling; Steel, Helen; Anderson, Ronald (Mediators of Inflammation, 2019)
Microbial lipopolysaccharides (LPS) have been implicated in the pathogenesis of rheumatoid arthritis (RA), possibly driving a systemic inflammatory response that may trigger the development and/or exacerbation of the disease. To explore the existence of this mechanism in African RA patients, we have measured systemic levels of LPS and its surrogate, LPS-binding protein (LBP), as well as those of intestinal fatty acid-binding protein (I-FABP), pulmonary surfactant protein D (SP-D), and cotinine in serum to identify possible origins of LPS, as well as associations of these biomarkers with rheumatoid factor (RF) and anticitrullinated peptide (aCCP) autoantibodies and the DAS 28-3 clinical disease severity score. A cohort of 40 disease-modifying antirheumatic drug-naïve, black South African RA patients rated by compound disease scores and 20 healthy subjects and 10 patients with chronic obstructive pulmonary disease (COPD) as controls were included in this study. Levels of the various biomarkers and autoantibodies were measured using a combination of ELISA and immunofluorimetric and immunoturbidometric procedures. LPS levels were lowest in the RA group compared to the healthy controls (p=0.026) and COPD patients (p=0.017), while LBP levels were also significantly lower in RA compared to the healthy individuals (p=0.036). Levels of I-FABP and SP-D were comparable between all three groups. Categorisation of RA patients according to tobacco usage revealed the following significant positive correlations: LBP with C-reactive protein (p=0.0137); a trend (p=0.073) towards an association of LBP with the DAS 28-3 disease severity score; RF-IgG antibodies with both LPS and LBP (p=0.033 and p=0.041, respectively); aCCP-IgG antibodies with LPS (p=0.044); and aCCP-IgG with RF-IgM autoantibodies (p=0.0016). The findings of this study, several of them novel, imply that tobacco products, as opposed to microbial translocation, represent a potential source of LPS in this study cohort of RA patients, again underscoring the risks posed by tobacco usage for the development and severity of RA.